Warehouse District along 1st Avenue N. (Minnesota Streetcar Museum)
1fcc44d35b3ba617e48f69b62cfaaa0d
United States
Minnesota
Hennepin
Downtown
Minneapolis
Keywords: streetcars; Twin City Rapid Transit Co.; street scene; Transportation